Antioxidant property of “Sweet Grape” tomatoes treated with heat shock - Cordeiro, Noélle Khristinne; Costa Braga, Gilberto; Carvalho, Jeferson Carlos; Souza Oliveira, Shirlene (Scientia Agraria Paranaensis, 2021)
Postharvest conservation methods such as heat shock can increase the nutritional profile of fruits, inducing greater accumulation of antioxidants that participate in the physiological maintenance of fruits. The objective of this work was to evaluate the antioxidant properties of “Sweet Grape” tomatoes treated with heat shock in pre-storage. “Sweet Grape” tomatoes were heat shocked in hot water (45°C) for 10 min. and stored at room temperature for 9 days. β-carotene, ascorbic acid, total phenolic compounds, and antioxidant activity (DPPH, ABTS, and FRAP) were evaluated every 3 days. The pulp and skin of the treated tomatoes had higher β-carotene content than the control during storage, according to the findings. The content of total phenolic compounds in the pulp reduced, regardless of the treatment. There was a reduction of ascorbic acid, but with significantly higher values ​​in the fruits treated on the third and sixth days of storage. The DPPH antioxidant activity of the pulp decreased, regardless of the treatment. In the skin there was a significant effect of the treatment until the sixth day. There was no variation in the ABTS antioxidant activity of the pulp of the treated tomatoes. There was no significant effect of heat shock on the FRAP antioxidant activity of the pulp until the sixth day. Heat shock promoted an increase in β-carotene in tomato skin, which was related to increases in its DPPH antioxidant activity. The heat shock treatment promoted greater retention of ascorbic acid in the fruit, but it was not able to avoid its reduction during storage. The tomatoes’ antioxidant biochemical response to heat shock is most expressed in their skin.